Lower cerebral oxygen utilization is associated with Alzheimer's disease-related neurodegeneration and poorer cognitive performance among apolipoprotein E ε4 carriers. Issue 4 (April 2022) - Robb, W Hudson; Khan, Omair A; Ahmed, Humza A; Li, Judy; Moore, Elizabeth E; Cambronero, Francis E; Pechman, Kimberly R; Liu, Dandan; Gifford, Katherine A; Landman, Bennett A; Donahue, Manus J; Hohman, Timothy J; et al.
Oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2 ) are markers of cerebral oxygen homeostasis and metabolism that may offer insights into abnormal changes in brain aging. The present study cross-sectionally related OEF and CMRO2 to cognitive performance and structural neuroimaging variables among older adults (n = 246, 74 ± 7 years, 37% female) and tested whether apolipoprotein E ( APOE )-ε4 status modified these associations. Main effects of OEF and CMRO2 were null (p-values >0.06), and OEF interactions with APOE -ε4 status on cognitive and structural imaging outcomes were null (p-values >0.06). However, CMRO2 interacted with APOE- ε4 status on language (p = 0.002), executive function (p = 0.03), visuospatial (p = 0.005), and episodic memory performances (p = 0.03), and on hippocampal (p = 0.006) and inferior lateral ventricle volumes (p = 0.02). In stratified analyses, lower oxygen metabolism related to worse language (p = 0.02) and episodic memory performance (p = 0.03) among APOE- ε4 carriers only. Associations between CMRO2 and cognitive performance were primarily driven by APOE- ε4 carriers with existing cognitive impairment. Congruence across language and episodic memory results as well as hippocampal and inferior lateral ventricle volume findings suggest that APOE -ε4 may interact with cerebral oxygen metabolism in the pathogenesis of Alzheimer's disease and related neurodegeneration.